Foster Youth Mentorship: A Qualitative Investigation Into Motivations and Experiences - Miranda, Cristina; Montes, Raquel; Contreras, Elizabeth; Mendoza, Pedro; Downey, Dennis (CBR@CSUCI: An annual volume of community-based research, 2019)
Research was conducted as a partnership between Casa Pacifica and the CSUCI Sociology Program as a senior capstone project. The research goal is to develop a better understanding of the experiences and motivations of volunteers serving foster youth, with specific interests in encouraging more volunteers to take on mentor roles. Research was based on qualitative interviews conducted with twenty volunteers who serve foster youth at Casa Pacifica – including ten members each of the Casa Pacifica Amigos and the California Youth Connection Adult Supporters. Members of both organizations were chosen in order to broaden the range of volunteer experiences and to facilitate informal comparisons. Interviews help us to understand volunteers’ understandings of mentorship and the sources of satisfaction in that activity; pathways to deepening involvement; and suggestions for encouraging more mentorship.